Legal-Economic Analysis of the Inability to Give Alms to the Family of Muhammad Because of Being the Relatives of the President - ÖZDİREK, Recep (Afro Eurasian Studies, 2018)
Alms/zakat is the financial worship of where it can be given fixed by the verses [of Qur’an]. The need of the poor, needy, stranded, mujahid, debtor who cannot pay their debt, and the alms officer are fulfilled from this item. Among those who cannot be given alms include the relatives of the Prophet. They cannot receive alms even if they cannot meet their basic needs. For them, allowances are allocated from the [war] booty and prize items of state income. In this article, which relatives of the Prophet are prohibited to take alms, the reasons behind it, and the justifications in the fiqh (Islamic law) books for that are going to be identified. The religious and legal grounds explained by the Fukaha (Islamic jurists) that Prophet accepted alms goods as “dirty” to those outside the allowed list will be determined and an attempt to make a new explanation will be made.
Keywords: Muhammad Family; Alms/Zakat; Prophet; Economic; Analysis; Din Araştırmaları; Religious Studies